Do qualitative changes in interlimb coordination lead to effectiveness of aquatic locomotion rather than efficiency? - Komar, J.; Sanders, R. H.; Chollet, D.; Seifert, L. (Journal of Applied Biomechanics, 2014)
This study compared interlimb coordination and indicators of swim efficiency and effectiveness between expert and recreational breaststroke swimmers. Arm-leg coordination of 8 expert and 10 recreational swimmers at two different paces, slow and sprint, were compared using relative phase between elbow and knee. For each participant, knee and elbow angles were assessed using a 3-dimensional video analysis system with four below and two above cameras. During each phase of the cycle, indicators of swim efficiency (intracyclic velocity variations) and effectiveness (horizontal distance, velocity peaks, acceleration peaks) were calculated. Two coordination patterns emerged between expert and recreational swimmers, with significant differences in the relative phase at the beginning of a cycle (-172.4° for experts and -106.6° for recreational swimmers) and the maximum value of relative phase (9.1° for experts and 45.9° for recreational swimmers; all P < .05). Experts` coordination was associated with higher swim effectiveness (higher acceleration peak: 2.4 m/s2 for experts and 1.6 m/s2 for recreational swimmers) and higher distance covered by the center of mass during each phase of the cycle (all P < .05). This study emphasized how experts coordinate arms and legs to achieve effective behavior, therefore exhibiting flexibility, mainly in the timing of the glide phase, to adapt to different speed.